Dialysis modality and survival: Done to death. Issue 4 (14th March 2018) - Trinh, Emilie; Chan, Christopher T; Perl, Jeffrey
Abstract: The debate surrounding whether peritoneal dialysis or hemodialysis is associated with differential survival continues as the numerous comparative studies over the past 3 decades have yielded conflicting results. Findings have also evolved over time in the setting of changing patient characteristics, advances in dialytic technologies, and the use of more robust statistical and epidemiologic approaches. Here, we will critically review the body of evidence, both historical and contemporary, comparing survival across dialysis modalities. Significant limitations of the observational nature of the current literature will be highlighted given that no adequately powered randomized controlled trials exist. Given the lack of consistency and limitations of current studies, coupled with the poor survival across both modalities, we can likely conclude that survival comparisons between both modalities do not appreciably differ. Hence, the choice of dialysis modality should not be dictated by survival comparisons, but rather be based on an individualized and informed decision making that places patient preference and lifestyle considerations at the forefront, while integrating medical factors and availability of resources and support. The emphasis of future research should move beyond survival outcomes when comparing dialysis modalities, and instead be redirected to patient‐endorsed and patient‐reported outcomes.